Kaynak Robotu Simulasyonu Ve Kontrolü - Öner, Hüseyin Ersel (Fen Bilimleri Enstitüsü, 1998)
Kaynak Robotu Simülayonu ve Kontrolü Bu çalışmada Türkiye'nin ilk endüstriyel amaçlı robotu HSR-6 robotunun, ark kaynağı işlemine uyarlanması amacıyla simülasyon ve kontrol uygulaması yapılmıştır. Robotun ters kinematik, dinamik ve kontrol analizleri yapılarak sistem davranışları incelenmiş ve HSR-6 robotunun kaynak uygulaması için ön çalışma yapılmıştır. Tüm proje boyunca kaynak işleminden bahsedilirken özel olarak belirtilmedikçe MAG kaynağı uygulaması gözönüne alınmıştır. İkinci bölümde kaynak işlemine ait temel bilgiler ve kaynak parametreleri incelenmiştir. Sanayide en çok kullanılan MAG kaynağı araştırmanın esas unsurunu oluşturmaktadır. Bu bölümdeki amaç ayrı bir uzmanlık gerektiren kaynak işleminin robot uygulaması için gerekli olan parametrelerinin belirlenmesi ve bu parametrelerin etkileşimlerinin incelenmesidir. Üçüncü bölümde antromorfik yapıya sahip olan HSR-6 robotunun genel kinematik hesaplamaları yapılmıştır. Robot referans duruşu için eksen takımları yerleştirilmiş ve Denavit- Hartenberg parametreleri seçilen eksen takımlarına göre belirlenmiştir. Kaynak torcu, kaynak açısı, ark boyu ve harmonik fonksiyon kinematik zincire eklenmiştir. Çalışmanın dördüncü aşamasında robotun, 3 boyutlu hareket sağlayan senaryo düşünülmüştür. Bunun için de zamana bağlı bir fonksiyon olan semer eğrisi seçilmiştir. Semer eğrisi denklemlerine göre maddesel nokta kinematiğinden eğrinin teğet, normal ve binormal vektörleri hesaplanmıştır. Elde edilen verilerle HSR-6 robotunun ters kinwmatik analizi çözümlenmiştir. Beşinci bölümde ters kinematik algoritmasıyla elde edilen eklem hareketleri,hızları ve ivme değerleriyle Lagrange- Eulerdinamiği kullanılarak motor momentleri hesaplanmıştır. Dinamik hesaplamaların ilk aşamasında herbir uzvun ataletleri redüksiyon oranı gözönünde bulundurularak motor ataletleriyle karşılaştırılmıştır. Altıncı bölümde ise MATLAB programında hazırlanan yazılım ile ilgili bilgiler ve program akış şeması verilmiştir. Yedinci bölümde etkileşimli incelenen ilk üç eksen için hesaplanmış moment kontrolü, bilek eksenleri için bağımsız PD kontrol algoritması uygulanmıştır.

As industry started using the latest technology, interference with robots in the automation systems became an inevitable need. In the age of superior inventions it is impossible to imagine most industrial applications without robots. In the overall world industry, welding is the application that is being most frequently robotized. Especially in the countries where automotive industry is highly developed the number of welding robots is deterministic. There are two main welding applications; arc welding applications and spot welding applications. The dominance of arc welding over spot or vice versa changes depending on the country. In Japan which is the country that owes 60% of the robot population of the world, arc welding applications are wider used than spot welding. Figure 1 HSR-6 General Purpose Anthropomorphic Robot In this project simulation and control work required in order to adopt the first Turkish industrial robot- HSR-6 to a welding application has been performed. Preliminary work needed for the welding application with HSR-6 and inverse kinematic, dynamic and control analysis have been done and the system behavior has been examined. Althrough the project when talking about welding operation if not specified MAG welding application has been taken into consideration. In the second section, basic knowledge about the welding operation has been given and the welding parameters have been examined. MAG welding, the most widely used welding application represents the main part. Factors affecting the quality of welding such as the working principles of the power units of MAG welding and the ways of transferring material have been explained. The aim in the second section is to figure out the parameters required in an expertized robot application and examine how these parameters influence one another. These predominant parameters are speed of welding, voltage of welding (therefore length of arc), torch angle, wire extension, diameter of electrode, weaving amplitude and weaving frequency. & /\ \ 'o \ ^ \ Figure 2. Welding Parameters(Welding Cross-Section Area and Weaving Amplitude) In the third part, general kinematic calculations concerning the anthropomorphic structure of the HSR-6 robot have been performed. The frame needed for the reference position of the robot has been selected and the Denavit-Hartenberg parameters suiting the selected frame have been figured out. Welding torch, welding Xlll angle, arc length and harmonic function have been added to the kinematic parameters chain. Figure 3- Anthropomorphic Robot Frame Selection In the forth part of the project, the scenario realizing the 3-D motion of the robot has been prepared. For the former reason a time dependent function- The horse saddle curve has been selected. x = r.cos(t) y = r.sin(t) = y[¥^: According to these equations, using material point kinematics, the tangent, normal and binomial vectors have been calculated. Using the resultant data the inverse kinematic analysis of the HSR-6 robot has been solved having parameters important fr the welding operation such as torch angle, arc length and harmonic weaving motion in addition XIV x-axis Figure 4- 3-D Horse Saddle Curve In the kinematic algorithm it has been assumed that the first three axes make up the wrist position, and the wrist axes provide the torch's angular position (Pieper's method). Later The kinematic solution of the first three axes has been calculated using the geometric approach. Using the angles of the first three axes found by the former operation, the angle values of the wrist axes can be found with the help of a direct kinematic calculation according to the Euler z-y-z. In the fifth part the motor moment values have been calculated using the joint motion's velocity and acceleration values resulting from the inverse kinematic algorithms together with Lagrange- Euler dynamics. In the first step of the dynamic calculations the inertia of each component has been compared with the motor inertia having in mind the reduction ratio. In the dynamic calculations the first three axes have been viewed as a dependent group and the remaining three axes- the wrist axes have been examined independently. During the dependent examination step, the inertia and weights of the 4th, 5th and 6th component since it has been considered that four of them represent single object. Having in mind the reduction ratio the dynamic calculations have been completed to yield the motor moment values and the graphs including those have been presented. In the sixth part the program written in MATLAB, some information about the software and the flow chart of the program have been presented. In the seventh part, "computed torque" control algorithm has been applied to the first three axes as dependent and P.D. control scheme has been applied to the remaining three axes as independent. XV Sampling time adjustment Curve selection Tangent, normal and binomial computation I General kinematic matrix generation i Addition of harmonic weaving, torch length, torch angle, arc length to the kinematic chain I Definition of the robot and work piece base frame according to the reference coordinate frame Inverse kinematic routine > Saving data Plotting joint movements Inverse dynamic routine Control sampling time adjustment Computed torque control algorithm T P. D. control algorithm i Motor dynamic Robot dynamic -m Saving data Plotting motor moments Figure 5- Prepared Program Flow Chart
Arc Welding Robot Similation And Control
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Kaynak; Robot denetim; Robot kinematiği; Robotlar; Welding; Robot control; Robot kinematics; Robots